1980
DOI: 10.1017/s0022149x00006386
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal development of Hymenolepis nana larvae in immunosuppressed mice

Abstract: Observations on the course of Hymenolepis nana infection in immunosuppressed mice are presented. Treatment of the host with hydrocortisone acetate caused superinfection of the bowel with worms and the development of normal cysticercoids in the mesenteric lymph node and liver. Natural infection of mice deprived of their T-cells by pre-adult thymectomy and administration of antithymocyte serum resulted in superinfection and widespread metastasis of aberrant cysticercoids that were greatly enlarged and without sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…The numbers of cysticercoids inoculated into mice in our study were consistent with other researchers who have reported successful infection to adult worm stages with 1±20 cysticercoids (Lucas et al, 1980;Ito et al, 1988;Kumazawa, 1992). Furthermore, in the present study, the consistent development of cysticercoids, obtained from the Japanese control isolate, into adult worms when inoculated into laboratory rodents indicated that the storage of cysticercoids in PBS prior to inoculation did not adversely affect the viability of the cysticercoids.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The numbers of cysticercoids inoculated into mice in our study were consistent with other researchers who have reported successful infection to adult worm stages with 1±20 cysticercoids (Lucas et al, 1980;Ito et al, 1988;Kumazawa, 1992). Furthermore, in the present study, the consistent development of cysticercoids, obtained from the Japanese control isolate, into adult worms when inoculated into laboratory rodents indicated that the storage of cysticercoids in PBS prior to inoculation did not adversely affect the viability of the cysticercoids.…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous research (Lucas et al, 1980;Ito et al, 1988;Asano et al, 1992;Maki & Ito, 1998) several different susceptible rodent hosts were used in the inoculation trials in this study. However, the use of these highly susceptible mice, even when further immunosuppressed with cortisone, and the use of hypothymic rodent hosts did not result in the development of eggs to either cysticercoid or adult worm stages in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact is of extreme relevance, taking into account that cestode infections induce very high levels of immunogenic responses in the parasitized animals (Lucas et al 1980, Ito, 1982). An interesting situation was observed in the inbred mice strains investigated: when the parasitism due to A. tetraptera reached high levels, those related to the infection with S. obvelata were low and vice-versa (Figs 5,8).…”
Section: Discussionmentioning
confidence: 99%
“…Among cestodiosis, one case of T. crassiceps invasive cysticercosis has been described in an AIDS patient, 17 as well as one case of disseminated cestodiosis initially diagnosed as sparganosis in an immunodeficient patient with Hodgkin’s disease receiving chemotherapy 5 . The parasite observed in this latter case was secondarily reconsidered to be probably similar to H. nana 18,19 . The peripheral blood and sputum of immunodeficient patients may contain cysticercoids of H. nana , suggesting wide dissemination 20 .…”
mentioning
confidence: 82%